Temporal patterns of childhood cancer survival 1991 to 2016: A nationwide register‐study based on data from the German Childhood Cancer Registry - Wellbrock, Maike; Spix, Claudia; Ronckers, Cécile M; Grabow, Desiree; Filbert, Anna‐Liesa; Borkhardt, Arndt; Wollschläger, Daniel; Erdmann, Friederike (International journal of cancer, 2023)
Childhood cancer is the leading disease‐related cause of death among under 15 year olds in Europe. Since primary preventive measures are lacking, improving survival probabilities and long‐term well‐being remain primary goals. With this report, we provide the first long‐term assessment and interpretation of patterns in childhood cancer survival in Germany, covering a period of 30 years. Using data from the German Childhood Cancer Registry, we assessed temporal patterns of cancer survival among children (0‐14 years) diagnosed in Germany from 1991 to 2016, by cancer type, age at diagnosis and sex. We calculated overall survival (OS) and average annual percentage changes of the respective 5‐year OS estimates. OS improved across all cancer types, age groups as well as for boys and girls over time. Five‐year OS for all childhood cancers combined increased from 77.8% in 1991‐1995 to 86.5% in 2011‐2016, with stronger improvements during the early 1990s. The most pronounced survival improvement was seen for acute myeloid leukaemia, at 2% annually and 5‐year OS recently reaching 81.5%. Survival improvements for some diagnoses such as neuroblastoma, renal tumours and bone tumours have flattened out. Tremendous enhancements in diagnostics, treatment and supportive care have affected average survival improvements for most cancer types. Recently, survival improvements have decelerated overall and for some cancer types, it plateaued at an unsatisfactory level. As not all children benefited equally from the survival improvements, personal factors (eg, socioeconomic circumstances, health literacy, access to care) likely affect individual prognosis and warrant further investigation. What's new? Aetiology and risk factors for many childhood cancers remain unknown. Thus, primary preventive measures for childhood cancer are lacking and improving survival probabilities and long‐term well‐being remain primary goals. In this investigation of childhood cancer patients in Germany, the authors examined relationships between survival patterns and diagnostic and therapeutic factors. Improvements in overall survival for all cancer types, across all age groups and sexes, were observed over time. For some cancer types, the rate of improvement has decelerated in recent years. The findings emphasise the impact of diagnostic and therapeutic enhancements on childhood cancer survival, but also revealed persistent inequalities.